Isla de calor nocturna de una ciudad mediterránea de interior: Inca (Mallorca) - Alomar-Garau, Gabriel; Rotger Pujades, Cristòfol; Aguiló Rodríguez, Marc; Lacomba Moreno, Neus (Geographicalia, 2021)
A new study of the urban heat island phenomenon applied to the Mallorcan city of Inca is presented, with the aim of expanding and verifying the results of previous works. Using the mobile transect method, measurements have been made in four respective seasons of the meteorological year: winter, autumn, summer and spring. The results confirm nocturnal heat islands that show temperature differences of up to 5.7º C between the central sector of the city and its rural surroundings. The urban anthropogenic activity in Inca, the reduced width of certain streets, the height of the buildings and the atmospheric stability, are combined factors that play in favor of this differential thermal increase, more pronounced in cold ambient conditions (autumn and winter) than of hot (spring and summer). The results are useful for urban planning works with environmental criteria.
Keywords: Urban heat island, urban climate, microcontinentality, Majorca, Inca